Pengembangan Program Bahasa Berbasis Managemen Kepengasuhan di SMP MBS Pondok Pesantren AN NUR Penatar Sewu Tanggulangin Sidoarjo - Muhlasin Amrullah; Vanda Rezania (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study is the development of caring-based language management, this research is classified as R & D (Research and Development) research which seeks to solve the problems the partners raised in this community service program are not all teachers who live in boarding school able to speak Arabic or English, or as a new boarding school SBM An Nur does not yet have a guide in the pattern of language application in boarding school the condition of the lack of a good language management system so that it has not been able to encourage students and boarding school residents to speak Arabic or English, including media that have not been maximized. In this program will offer solutions that are expected to solve partner problems. The main method used is the development of language management systems in boarding school with caring based management. The results of this community service program are partners who have language management systems that are able to encourage students and boarding school residents to speak Arabic and English correctly